Union Impact on Job Tenure - Zhang, Yicheng (Université d'Ottawa | University of Ottawa, 2010)
This paper examines that impact of union membership on workers' job tenure in Canada. Using the 2008 Labour Force Survey, I find union membership has a positive impact on a worker's tenure. Females, seniors and the less educated are the three groups which